Reviewed on Combustion Modelling of Marine Spark-Ignition Engines - Nekooei, Mohammad Javad; Koto, Jaswar; Priyanto, A.; Dehghani, Zahra (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2015)
This research reviewed combustion modelling of marine sparkignition engine using mass fraction burned based on Wiebe function approach. In the paper, firstly, the cylindrical pressure is discussed and correlated function of engine operation condition. The cylinder pressure signal was constructed as a function of crank angle over an engine operational map. The parameters of the cylindrical pressure model were calibrated with s-curve matching techniques. The objectives of the research was to construct a combustion model on the cylindrical pressure suitable for control oriented model.